The Concept of the Transmission, Preservation, and Development of Traditional Arts and Culture in The Era of Digital Technology - Saefurrhman, Nandi (MSJ : Majority Science Journal, 2026)
This study examines the integration of digital technologies in cultural heritage preservation within the context of sustainability and community engagement. The rapid development of digital media, artificial intelligence, and interactive platforms has transformed the ways cultural heritage is preserved and transmitted; however, challenges related to authenticity, inequality, and cultural commodification remain significant. This research employs a qualitative descriptive-analytical method using a systematic literature review approach. Data were collected from reputable academic journals and analyzed through thematic and content analysis, including data reduction, categorization, and triangulation of sources. The findings reveal that digital technologies such as social media, AI, augmented reality, and digital documentation significantly enhance accessibility, innovation, and cultural awareness. However, issues such as the loss of cultural meaning, unequal technological access, and limited representation of intangible heritage persist. The discussion highlights that effective digital transformation must integrate community participation, interdisciplinary approaches, and ethical considerations to ensure sustainability. In conclusion, digital technologies can serve as strategic tools for preserving and innovating cultural heritage if implemented in a balanced manner that maintains authenticity and empowers local communities. Sustainable cultural preservation in the digital era requires the alignment of technological advancement with cultural values and participatory frameworks.